Potent and Selective Fluoroketone Inhibitors of Group VIA Calcium-Independent Phospholipase A(2) - Kokotos, George (2010)
Group VIA calcium-independent phospholipase A(2) (GVIA iPLA(2)) has recently emerged as a novel pharmaceutical target. We have now explored the structure-activity relationship between fluoroketones and GVIA iPLA(2) inhibition. The presence of a naphthyl group proved to be of paramount importance. 1,1,1-Trifluoro-6-(naphthalen-2-yl)hexan-2-one (FKGK18) is the most potent inhibitor of GVIA iPLA(2) (X(I)(50) 0.0002) ever reported. Being 195 and >455 times more potent for GVIA iPLA(2) than for GIVA cPLA(2) and GV sPLA(2), respectively, makes it a valuable tool to explore the role of GVIA iPLA(2) in cells and in vivo models. 1,1,1,2,2,3,3-Heptafluoro-8-(naphthalene-2-yl) octan-4-one inhibited GVIA iPLA(2) with a X(I)(50) value of 0.001, while inhibiting the other intracellular GIVA cPLA(2) and GV sPLA(2) at least 90-times less potently. Hexa- and octa-fluoro ketones were also found to be potent inhibitors of GVIA iPLA(2); however they are not selective.